Epidemiological Profile of Patients Presented with Traumatic Brachial Plexus Injury in a Tertiary Care Center: A Descriptive Cross-sectional Study - Batajoo, Santosh; Shrestha, Niresh; Shrestha, Om Prasad (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND Traumatic brachial plexus injuries are devastating injuries often resulting from high velocity road traffic accidents that may lead to severe functional disability. Despite continuous evolution in the surgical technique, the clinical outcomes following these injuries remain poor, especially in developing countries due to a lack of enough information in the literature regarding patients and injury characteristics. This study aims to evaluate epidemiological profile of the patients presented with traumatic brachial plexus injury in a tertiary care center. METHODS A descriptive cross-sectional study was conducted at B.&B. Hospital, Gwarko, Lalitpur, Nepal, between January 1, 2020, and December 31, 2023. Hospital in-patient electronic data record was screened using keyword “brachial plexus injury”. Adult patients (Age>18 years) with traumatic brachial plexus injury were included. Patients with missing information on demographic parameters, admission for other reasons, and who did not receive surgical treatment were excluded. The data were collected between March 1, 2024, and March 31, 2024. Convenient sampling technique was used and all eligible participants within the study period were included. Descriptive statistics were used, and continuous data were reported in mean and categorical data were expressed in numbers and percentage. RESULTS A total of 38 patients were included in the study. The mean age of the patients was 27.6 years, ranging from 18 to 59 years. There were 31 (81.6%) were male and 7 (18.4%) were female. 36 (94.7%) were due to road traffic accidents. Out of 36, 34 (94.5%) were of two-wheelers. 28 (73.7%) were part of polytrauma and 10 (26.3%) were isolated. Twenty-one (51.2%) had global pattern. 13 (34.2%) received nerve transfer and 6 (15.8%) received nerve transfer with graft. CONCLUSION Traumatic BPI is common among young males riding two-wheelers. C5-T1 is the most common injury pattern. Neurotization remains the gold standard primary treatment, with SAN to SSN transfer is the most performed surgery.